Spermine Oxidase–Substrate Electrostatic Interactions: The Modulation of Enzyme Function by Neighboring Colloidal ɣ-Fe2O3 - Graziano Rilievo; Massimiliano Magro; Federica Tonolo; Alessandro Cecconello; Lavinia Rutigliano; Aura Cencini; Simone Molinari; Maria Luisa Di Paolo; Cristian Fiorucci; Marianna Nicoletta Rossi; Manuela Cervelli; Fabio Vianello (Biomolecules, 2023)
Protein–nanoparticle hybridization can ideally lead to novel biological entities characterized by emerging properties that can sensibly differ from those of the parent components. Herein, the effect of ionic strength on the biological functions of recombinant His-tagged spermine oxidase (i.e., SMOX) was studied for the first time. Moreover, SMOX was integrated into colloidal surface active maghemite nanoparticles (SAMNs) via direct self-assembly, leading to a biologically active nano-enzyme (i.e., SAMN@SMOX). The hybrid was subjected to an in-depth chemical–physical characterization, highlighting the fact that the protein structure was perfectly preserved. The catalytic activity of the nanostructured hybrid (SAMN@SMOX) was assessed by extracting the kinetics parameters using spermine as a substrate and compared to the soluble enzyme as a function of ionic strength. The results revealed that the catalytic function was dominated by electrostatic interactions and that they were drastically modified upon hybridization with colloidal ɣ-Fe2O3. The fact that the affinity of SMOX toward spermine was significantly higher for the nanohybrid at low salinity is noteworthy. The present study supports the vision of using protein–nanoparticle conjugation as a means to modulate biological functions.